2020
DOI: 10.1155/2020/8150718
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Cultural Adaptation and Face Validity of the Functional Mobility Assessment into Brazilian Portuguese

Abstract: Introduction. The Functional Mobility Assessment (FMA) measures satisfaction with mobility devices in daily life. However, in Brazil, there is a lack of instruments which measure functional mobility. Objective. We aim to report the cross-cultural adaptation process and face validity of the FMA for use in Brazil. Methods. Two international guidelines were used in the cross-cultural adaptation process. Two independent translators translated the instrument from English to Brazilian Portuguese, and the two version… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 28 publications
(36 reference statements)
1
6
0
Order By: Relevance
“…This included measuring the face validity of the adapted PIC-ME for UO children, by examining the degree to which the participants understood the tool's statements and depictions after the cultural adaptations were made. Similar confirmation was performed in research by Paulisso et al [67]. Results indicated that most participants agreed that the statements described what they saw in the pictures.…”
Section: Discussionsupporting
confidence: 87%
“…This included measuring the face validity of the adapted PIC-ME for UO children, by examining the degree to which the participants understood the tool's statements and depictions after the cultural adaptations were made. Similar confirmation was performed in research by Paulisso et al [67]. Results indicated that most participants agreed that the statements described what they saw in the pictures.…”
Section: Discussionsupporting
confidence: 87%
“…Because of the randomization and the fact that there are 10 questions with 7 possible answers in the FMA, we believe that the recall of the answer would not influence the results. Furthermore, our study used a relatively larger sample size compared to the previous studies that translated the FMA into other languages [31][32][33]. The results were statistically significant with moderate agreement between the scores obtained in English and Arabic FMA tools.…”
Section: Discussionmentioning
confidence: 75%
“…It has been very helpful in quantifying the impact of mobility devices in the functional performance of the individuals during performing different activities of daily living (ADLs) and instrumental activities of daily living (IADL) [31]. The FMA was also translated into Brazilian Portuguese language and demonstrated helpful valid and reliable data [32,33]. Additionally, the FMA was adapted for use with schoolaged pediatric population of wheelchair users in Africa and provided a reliable information that helped better understand children needs and their caregivers while using their wheelchairs [34].…”
Section: Discussionmentioning
confidence: 99%
“…From the CHWs/OTLs ratings, we calculated separately for the CHWs and OTLs the agreement index as the mean scores of ratings of the extent to which CHWs/OTLs agreed that the tool covers everything that happens on household visits (agreed) and how many were happy to be assessed using the tool (happy). The agreement index should be ≥85% ( 43 ) otherwise, the tool should be revised if the index is <85%.…”
Section: Methodsmentioning
confidence: 99%